Socioeconomic status as a moderator between frailty and mortality at old ages. Issue 1 (December 2016) - Gu, Danan; Yang, Fang; Sautter, Jessica
Abstract Background Despite the well-established power of frailty to predict mortality, and the known associations of socioeconomic status (SES) with mortality, it is largely unknown whether the linkage between frailty and mortality varies across different SES groups. This study aims to investigate whether SES moderates the association between frailty and mortality. Methods We relied on the 2008/2009 and 2011/2012 waves of the Chinese Longitudinal Healthy Longevity Survey, a nationwide sample of 13, 731 adults aged 65 or older in China. Frailty was constructed using a cumulative index of 38 items (with 39 deficits) reflecting different dimensions of health; the index or the proportion of deficits ranges from 0 to 1, with greater scores indicating poorer health condition. SES was measured by a socioeconomic vulnerability index (SEVI) also from a similar cumulative approach consisting of 6 deficits; the proportion of deficits ranges from 0 to 1 with higher scores indicating lower SES. Eight Weibull hazard regression models were performed to examine how SES moderates the linkage between frailty and mortality. Results We found that a one percentage point increase in the frailty index was associated with an increased hazard ratio (HR) by 2.7 % (HR = 1.027, 95 % CI: 1.025–1.027); a one percentage point increase in SEVI score was associated with an increased hazard ratio by 0.6 % (HR = 1.006, 95 % CI: 1.004–1.008) controlling for demographics. When interactions between SEVI and frailty index were modeled, the increased mortality risk associated with frailty was weaker among people with lower SES than among people with higher SES (HR = 0.983, 95 % CI: 0.967–0.992). However, the moderating role of SES was diminished when interactions between SES and age and between frailty and age were modeled. With increasing age, the increased mortality risks associated with frailty and socioeconomic vulnerability weakened. Conclusions Frailty was a stronger predictor of mortality among individuals with higher SES than those with lower SES. The increased mortality risks associated with socioeconomic vulnerability and frailty weakened with age. Public health programs aimed at improving SES and promoting healthy longevity should start early in old age, or even earlier, and target poor and frail older adults for maximum impact.